Perinatal mental health in India in the states of Haryana and Telangana: A district-level situational analysis - Lucy Mellers; Sudhir Raj Thout; Sandhya Kanaka Yatirajula; Jane Hirst; Devarsetty Praveen; Pallab K Maulik; Vinod Bobji; Nicole Votruba (Cambridge Prisms: Global Mental Health)
Women in the perinatal phase are at an increased risk of experiencing mental health problems, but in low and middle-income countries such as India, perinatal mental health (PMH) care provision is often scarce. This situational analysis presents the formative findings of the SMARThealth Pregnancy and Mental Health (PRAMH) project (Votruba et al. 2023). It investigates the nature and availability of maternal mental health policies, legislation, systems and services, as well as relevant context and community in India on a national, state (Haryana and Telangana) and district (Faridabad and Siddipet) level. A desktop, scoping review and informal interviews with mental health experts were conducted. Socio-demographic and maternal health indicators vary between Haryana and Telangana. No specific national PMH policy or plan is available. General mental health services exist at a district level within Siddipet and Faridabad, but no specific PMH services have been identified.